Hubungan Tingkat Kematangan dengan Sisa Makanan Pokok pada Pasien Anak di RUMKITAL Dr. Ramelan Surabaya - Fathia Rabbani (Amerta Nutrition, 2018)
Background: The plate waste is one indicator of the success of the  food management in hospitals. Currently, there are still many hospitals that have plate waste over 20%.  Staple food is a food that is often not eaten by the patient. This can be caused by the level of ripeness that is less appropriate. Objective: To analyze the correlation between level of ripeness  with  the plate waste of staple food  among pediatric patients in Dr. Ramelan Surabaya Naval Hospital. Methods: This study used an observational study design with cross sectional study design. The sample size was 34 respondents. The samples in this study were children aged 2-12 years and treated in second- and third-class hospital wards. This was a cross sectional study involving 34 respondents at the RUMKITAL Dr. Ramelan Surabaya. The samples in this study were children aged 2-12 years old. Plate waste of staple food was collected for measurement using comstock method; level of ripeness were measured using questionnaires. Statistical analysis used was Chi Square test.Results: The average of respondents’ plate waste which shows the level of ripeness as inappropiate, appropriate, and very appropriate are 100%, 62%, dan 33%. This resea rch founds that there is a significant relation between the level of ripeness (p=0.024) with the plate waste of staple food. Conclusions: There is a significant relation between the level of ripeness (p=0.024) with the plate waste of staple food among pediatric patients Rumkital Dr. Ramelan Surabaya. The level of ripeness can cause the texture of the staple food served to be inappropriate so that the pediatric patients become lazy to spend it.ABSTRAKLatar Belakang: Sisa makanan termasuk dalam indikator keberhasilan penyelenggaraan makanan rumah sakit. Sekarang, masih terdapa banyak rumah sakit dengan tingkat sisa makanan dalam kategori banyak yaitu >20%. Makanan pokok merupakan makanan yang paling banyak jumlah sisanya. Hal tersebut dapat disebabkan oleh faktor tingkat kematangan yang kurang sesuai.Tujuan: Untuk menganalisis hubungan antara tingkat kematangan dengan sisa makanan pokok pada pasien anak di Ruang Rawat Inap RUMKITAL Dr. Ramelan Surabaya.Metode: Penelitian ini menggunakan rancangan penelitian cross sectional. Besar sampel penelitian sebanyak 34 responden. Sampel adalah pasien anak berusia 2-12 tahun. Sisa makanan pokok dihitung dengan metode comstock; tingkat kematangan makanan didapat melalui wawancara dan kuesioner. Uji statistik yang digunakan adalah uji Chi square.Hasil: Rerata jumlah sisa makanan responden yang menyatakan tingkat kematangan kurang sesuai, sesuai, dan sangat sesuai yaitu sebesar 100%, 62%, dan 33%. hubungan yang signifikan antara tingkat kematangan (p=0,024) dengan sisa makanan pokok didapatkan melalui penelitian ini.Kesimpulan: Tingkat kematangan memiliki hubungan yang signifikan dengan sisa makanan pokok pada pasien anak Rumkital Dr. Ramelan Surabaya. Tingkat kematangan dapat menyebabkan tekstur makanan pokok yang disajikan tidak sesuai sehingga pasien anak menjadi malas untuk menghabiskannya.